Conversion of antibacterial activity of graphene‐coated textiles through surface polarity - Daniela P. Rodrigues; Catarina Moreirinha; Gopika Rajan; Ana I. S. Neves; Sidónio C. Freitas; Sara Sequeira; Saverio Russo; Monica F. Craciun; Adelaide Almeida; Helena Alves (Nano Select, 2023)
Abstract Graphene is emerging in numerous wearable and biomedical applications. Understanding the impact of graphene‐based nanocomposites over bacterial activity is critical for design appropriate technical solutions. In this work, antibacterial activity of monolayer and few‐layer graphene is tested against Gram‐negative and Gram‐positive model bacteria. Such graphene‐based nanomaterials present different effects on bacteria viability, depending on concentration and shape. The presence of dopant agents can either increase or revert graphene antibacterial effect. Among other bactericidal mechanisms, we also demonstrate that graphene surface polarity is connected to antibacterial properties and can be easily modified by surface charge transfer doping. This electrophilicity tuning offers a novel mechanism for the molecular basis of graphene's antibacterial activity.